Growth, real exchange rates and trade protectionism since the financial crisis - Georgios Georgiadis; Johannes Gräb (European Central Bank (ECB), 2013)
Existing evidence suggests that protectionist activity since the financial crisis has been muted, raising the question whether the historically well-documented relationship between growth, real exchange rates and trade protectionism has broken down. This paper re-visits this relationship for the time period since 2009. To this end, we use a novel and comprehensive dataset which considers a wide range of trade policies stretching beyond the traditionally considered tariff and trade defence measures. We find that the specter of protectionism has not been banished: Countries continue to pursue more trade-restrictive policies when they experience recessions and/or when their competitiveness deteriorates through an appreciation of the real exchange rate; and this finding holds for a wide array of contemporary trade policies, including “murky” measures. We also find differences in the recourse to trade protectionism across countries: trade policies of G20 advanced economies respond more strongly to changes in domestic growth and real exchange rates than those of G20 emerging market economies. Moreover, G20 economies' trade policies vis-à-vis other G20 economies are less responsive to changes in real exchange rates than those pursued vis-à-vis non-G20 economies. Our results suggest that—especially in light of the sluggish recovery—the global economy continues to be exposed to the risk of a creeping return of trade protectionism.
Keywords: F13; F14; 330; exchanges rates; growth; trade protectionism